2017
DOI: 10.1016/j.jval.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effectiveness and Cost Effectiveness of Organized versus Opportunistic Screening for Breast Cancer in Austria

Abstract: The decision to adopt organized screening is likely an efficient use of limited health care resources in Austria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…Patients identified as false positive or false negative are particularly difficult to consider in cost-effectiveness analysis given the lack of data on these patients. Costs and outcomes for patients who followed incorrect screening and treatment pathways were included in 22 (32.3%) of the studies [ 12 , 17 , 18 , 21 , 23 25 , 29 , 36 , 40 , 42 , 43 , 45 54 ]. Even though some cost-effectiveness analyses identified false positives in the screening pathways, one alternative was to assume 100% accurate diagnostic tests; this meant patients identified incorrectly during screening would never go on to inappropriate treatment [ 29 , 42 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients identified as false positive or false negative are particularly difficult to consider in cost-effectiveness analysis given the lack of data on these patients. Costs and outcomes for patients who followed incorrect screening and treatment pathways were included in 22 (32.3%) of the studies [ 12 , 17 , 18 , 21 , 23 25 , 29 , 36 , 40 , 42 , 43 , 45 54 ]. Even though some cost-effectiveness analyses identified false positives in the screening pathways, one alternative was to assume 100% accurate diagnostic tests; this meant patients identified incorrectly during screening would never go on to inappropriate treatment [ 29 , 42 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that in 2016 the mammography-screening program in Kazakhstan was cost-effective with the incremental costeffectiveness ratio equaled to USD 3,157. Mammography screening has proven to be effective in several developed countries (Nyström et al, 1993;Fracheboud et al, 2003;Fruehwirth et al, 2017;Arrospide et al, 2016). However, the cost-effectiveness of mammography screening programs in post-Soviet economic transitional countries such as Kazakhstan is absent.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Table 7 demonstrates the sensitivity analysis using 5 parameters. At the same time, based on a willingness-to-pay a threshold of triple the GDP, a total of USD 22,530 per life-year-gained in 2016, the mammography screening is cost-effective (Schiller-Fruehwirth et al, 2017). However, as the willingness-to-pay is associated with income and circumstances, the cost-effectiveness threshold based on willingness-to-pay was not utilized in this study (Wagnera et al, 2000).…”
Section: Sensitivity Analysismentioning
confidence: 98%
“…After age and genetic factors, such as BRCA status, a linear increase in breast density, which means that women with a Breast Imaging Reporting and Data System (BI-RADS) category of D are associated with a four- to sixfold increase in the risk of breast cancer compared to women in the lowest density group, BI-RADS A ( 36 ). Health authorities have recognized the relevance and impact of breast density in screening and, in some countries, supplemental screening methods for women with dense breasts (ACR categories C and D) have been introduced ( 37 39 ). In this context, it also stands to reason that breast density may be used for individual risk assessment and tailored screening strategies ( 10 , 12 , 34 , 35 ).…”
Section: Breast Densitymentioning
confidence: 99%
“…The Japan Strategic Anti-Cancer Randomized Trial (J-STAT) investigated the efficacy of additional US in a large nationwide screening program for breast cancer, with a significantly higher breast cancer detection rate, a lower number of interval cancers, and the detection of additional cancers, compared to mammography alone, in women aged 40–49 years ( 84 ). In addition, Austria started a nationwide biannual mammography screening program offering additional US for those with density categories C and D. Initial results are expected to be presented soon ( 39 ). To overcome the observer-dependency of hand-held supplemental screening US, automated, 3D, whole-breast US (ABUS) has been introduced ( 85 87 ).…”
Section: Supplemental Screening Modalitiesmentioning
confidence: 99%